The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2139/ssrn.3224323
|View full text |Cite
|
Sign up to set email alerts
|

Global Online Piracy Study

Abstract: The survey deals with the acquisition and consumption of music, films, series, books and games through the various legal and illegal channels that exist nowadays. The illegal channels studied are downloading and streaming from illegal sources (including via dedicated technical devices), and streamripping. The study was made possible by financial support from Google and builds on previous studies by IViR and Ecorys for the Dutch Government and the European Commission. In the latter, a comparable survey was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…Daugiausia tiriama nelegaliai platinamos skaitmeninės muzikos (LaRose & Kim, 2007;Lysonski & Durvasula, 2008), filmų (Bai & Waldfogel, 2012;Chellappa & Shivendu, 2003;Jacobs, Heuvelman, Tan, & Peters, 2012), programinės įrangos (Cronan & Al-Rafee, 2008;Mishra, Akman, & Yazici, 2006;Proserpio, Salvemini, & Ghiringhelli, 2005) naudojimas. Daugeliu atvejų tam naudojami statistiniai duomenys ir tiriamas nelegaliai platinamo turinio vartotojų elgesys (Cronan & Al-Rafee, 2008;Jacobs et al, 2012;LaRose & Kim, 2007;Phau, Teah, & Lwin, 2014;Taylor, 2012;Taylor, Ishida, & Wallace, 2009). Kai kurie tyrimai koncentruojasi į lyčių elgesio skirtumus (Bouhnik & Mor, 2014;Morris, Johnson, & Higgins, 2009) ar piratų bendruomenių narių elgseną (Diamant-Cohen & Golan, 2017).…”
Section: įVadasunclassified
See 2 more Smart Citations
“…Daugiausia tiriama nelegaliai platinamos skaitmeninės muzikos (LaRose & Kim, 2007;Lysonski & Durvasula, 2008), filmų (Bai & Waldfogel, 2012;Chellappa & Shivendu, 2003;Jacobs, Heuvelman, Tan, & Peters, 2012), programinės įrangos (Cronan & Al-Rafee, 2008;Mishra, Akman, & Yazici, 2006;Proserpio, Salvemini, & Ghiringhelli, 2005) naudojimas. Daugeliu atvejų tam naudojami statistiniai duomenys ir tiriamas nelegaliai platinamo turinio vartotojų elgesys (Cronan & Al-Rafee, 2008;Jacobs et al, 2012;LaRose & Kim, 2007;Phau, Teah, & Lwin, 2014;Taylor, 2012;Taylor, Ishida, & Wallace, 2009). Kai kurie tyrimai koncentruojasi į lyčių elgesio skirtumus (Bouhnik & Mor, 2014;Morris, Johnson, & Higgins, 2009) ar piratų bendruomenių narių elgseną (Diamant-Cohen & Golan, 2017).…”
Section: įVadasunclassified
“…Daugelis nelegaliai platinamų skaitmeninių knygų naudojimo tyrimų atlikta didelių šalių rinkose: JAV (Lysonski & Durvasula, 2008), Kinijos (Bai & Waldfogel, 2012), Ispanijos (Camarero et al, 2014), Australijos (Phau et al, 2014), Pietų Korėjos (Lee, Fenoff, & Paek, 2019;Yoon, 2011), Jungtinės Karalystės (Brunton-Smith & McCarthy, 2016, Vokietijos (Jonas & Sirkeci, 2018). O tyrimų, kurie analizuotų nelegaliai platinamų skaitmeninių knygų naudojimą mažų kalbų rinkose, trūksta.…”
Section: įVadasunclassified
See 1 more Smart Citation
“…Although the development of the internet architecture facilitates data exchange, it may also lead to a higher risk of copyright infringement. This threat has attracted a lot of attention to copyright protection [1], [2]. In [2] Poort et al reported that more than 60% of audio-visual books, music and other digital content have been acquired illegally.…”
Section: Introductionmentioning
confidence: 99%
“…There are many possible explanations for why online book piracy is rarely in the headlines: e-book markets and audiences are still relatively small compared to print; electronic reading device penetration is much lower than mp3 players and the like; and print is probably still a preferred format for many. Yet, while e-book piracy is definitely present, its volume and economic value is perceived as low, especially compared to the losses suffered by the music and audiovisual sectors [ 31 ]. E-book black markets failed to develop their own Napster service, and book piracy sites have remained local, fragmented and marginal.…”
Section: Introductionmentioning
confidence: 99%